The Association of Vitamin D with Metabolic Syndrome in Adults with Prediabetes (Bangladesh Journal of Medicine, 2021)
Background: Vitamin D may play important role in the pathogenesis of several components of metabolic syndrome (MS). The aim of this study was to observe the association of vitamin D with MS and its components in Bangladeshi adults with prediabetes.Methods: This cross-sectional study was done among 117 newly detected nonpregnant adults with prediabetes [age (years): 36.30±9.99; BMI (kg/ m2): 28.89±4.35, mean±SD; M/F: 23/94] based on American Diabetes Association 2018 criteria. Metabolic syndrome was diagnosed by any three of five criteria: central obesity; elevated blood pressure, fasting blood glucose & triglyceride (TG) and lower HDL cholesterol. Glucose was measured by glucose oxidase, lipid by glycerol phosphate dehydrogenase-peroxidase and vitamin D by high performance liquid chromatography method. Vitamin D